APPLICATION OF THE PRINCIPLES OF GOOD GOVERNANCE TO THE EFFECTIVENESS OF EMPLOYEE PERFORMANCE AT THE DEPARTMENT OF AGRICULTURE, FOOD SECURITY, AND FISHERIES, PONOROGO REGENCY - Yulistiana, Munika Marga Utama; Utomo, Supri Wahyudi; Wihartanti, Liana Vivin (Fakultas Ekonomi dan Bisnis, Universitas Jenderal Soedirman, 2022)
Good governance patterns and good governance are demands and needs in governance. The aims of this study are: 1) to analyze the effect of participation on the effectiveness of employee performance, 2) to analyze the effect of transparency on the effectiveness of employee performance, 3) the effect of accountability on the effectiveness of employee performance, and 4) the influence of grasping power on the effectiveness of employee performance. The research method used is causal quantitative and the type of data used is primary data. A sample of 50 respondents was taken from the finance department, personnel and general department, the program composition section, the plant section and horticulture with purposive sampling method. partial test is used. Based on the test results, it shows that partially participation affects the effectiveness of employee performance, transparency affects the effectiveness of employee performance, accountability affects the effectiveness of employee performance, and capture power affects the effectiveness of employee performance.